Distributing regionally, distinguishing locally: examining the underlying effects of local land use on airborne bacterial biodiversity. (9th September 2018) - Docherty, Kathryn M.; Pearce, Douglas S.; Lemmer, Kristina M.; Hale, Rebecca L.
Summary: Airborne bacteria are abundant and can vary with land use. Urban expansion is increasing rapidly at a global scale, altering natural sources of airborne bacterial biodiversity, as soils and native plants are replaced by pavement and managed yards. Urbanization homogenizes the biodiversity of larger organisms, but its effects are understudied with respect to microbes. This study uses categorical and gradient approaches to examine airborne bacterial communities in southwest Michigan (USA). Airborne communities carried a gut‐microbial signature and were equally homogenous above urban and rural sites, despite greater homogeneity of soil communities at urban sites. Ruminococcaceae were abundant, the source of which is likely wildlife. Beyond the gut‐microbial signature, there were underlying effects of land use, which were evident in the shared airborne taxa across urban and rural sites. Bacillales, Burkholderiales, Alteromonadales and Pseudomonadales were shared more across urban sites, while Xanthomonadales, which contains crop‐plant pathogens, were shared across rural agricultural sites. These results suggest that taxa which may distribute globally, coupled with localized sources, contribute to urban communities, while regional rural activities drive rural composition. We determined that soils were unlikely to contribute to broad distribution of some plant‐associated taxa, but may be a source for distribution of others.